Effect of Zn(O, S) buffer layer thickness on charge carrier relaxation dynamics of CuInSe2 solar cell. (May 2015) - Sun, Juan; Nalla, Venkatram; Nguyen, Mai; Ren, Yi; Chiam, Sing Yang; Wang, Yue; Tai, Kong Fai; Sun, Handong; Zheludev, Nikolay; Batabyal, Sudip K.; Wong, Lydia H.
Abstract : Graphical abstract: Highlights: We observed Zn(O, S) is a promising buffer layer for CIGS type photovoltaic's devices. Thinner chemical bath deposited-Zn(O, S) works better for the CuInSe2 solar cell. S to O compositional gradient is observed in the CBD grown Zn(O, S) buffer layer. The carrier lifetime is higher for the device with thinner Zn(O, S) buffer layer. Abstract: A pinhole free Zn(O, S) buffer layer was deposited on CuInSe2 (CIS) absorber by chemical bath deposition (CBD) method. Thin Zn(O, S) exhibits better power conversion efficiency (PCE) at lower thickness. Enhancement of PCE from 1.5% to 3.9% was observed for electrodeposited CIS photovoltaic device when the buffer layer thickness reduces from 50 nm to 20 nm. Although the conduction band offset (CBO) at Zn(O, S)/CIS interface are almost identical for both the 20 nm and 50 nm thick buffer layers, investigation on charge carrier dynamics reveals that the carrier lifetime for the 20 nm buffer is much longer than the 50 nm buffer. This offers a plausible explanation for the higher J sc of the device with 20 nm buffer layer compared to the device with 50 nm buffer layer.